(untitled) (Al-Qamar, 2024)
In Islamic Studies, the status of Hadith comes next to the Holy Quran. The teachings of Quran are interpreted in the light of Hadith. Moreover, all commandments and queries of Shariah have come through Hadith. In the beginning of Islam, the Muslims considered the Hadith as the most important source of knowledge. In this regard, Muhaddiseen offered such services and wrote such books as ever exemplified in the history of the world. It is fact that the concoction of Hadith started in the Nabvi Era and continued till the period of followers (Tabeen). There were multi-dimensional motives behind this evil like lust, atheism, religious biasness, sectarian indifferences, fame and obedience of kings and rulers etc. Muhadditheen face this evil’s challenge with zeal and zest in every era of the Islamic history. They framed the best principles to overcome the situation for the safeguard the Hadith. In this regard, the Muhadditheen of the Sub-continent played an unforgettable and historical role. So that I have discussed the concocted the Hadith in this article. The article is so informative and enlightening that the reader feels it useful in this field. Particularly, the Sub-continent has always played a vital role in this regard, for the most authentic books of Hadith have come from this part of the world.